ANALISIS KEAKTIFAN SISWA TERHADAP MODEL PBL PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS IV SD ISLAM AL MADINA SEMARANG - Shella Tasya Hidayatul Adkia; Ikha Listyarini; Windyati; Arfilia Wijayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The background that prompted this research was the fourth grade students of Al Madina Islamic Elementary School, Semarang, who had very good learning activity. Class IV students were very enthusiastic when learning took place. This can be seen from the students' responses when the teacher asks a small question and the students will scramble to raise their hands to answer the teacher's question. Then the researchers wanted to find out whether the application of the Problem Based Learning learning model made students more active in learning Indonesian. Apart from that, researchers also want to know what factors influence the learning activities of fourth grade students at Al Madina Islamic Elementary School, Semarang. This type of research is descriptive qualitative. Data collection in this research was carried out using the methods: interviews, observation, questionnaires and documentation. The results of research based on interviews with teachers say that students are more active when implementing the Problem Based Learning learning model.